2014
DOI: 10.5114/ceji.2014.47725
|View full text |Cite
|
Sign up to set email alerts
|

Experimental immunology Exposure to hypergravity increases serum interleukin-5 and pulmonary infiltration in mice with allergic asthma

Abstract: ObjectiveWe evaluated the effect of acute hypergravity (HG) on the immune response in a murine model of allergic asthma.Material and methodsTwenty-eight BALB/c mice were used. Group A (control group, n = 7) mice were sensitized and challenged with normal saline. Group B (control HG exposure group, n = 7) mice were sensitized, challenged with saline, and exposed to acute HG (+10 Gz) for 4 hours. Group C (asthma group, n = 7) mice were challenged with intraperitoneal and intranasal ovalbumin (OVA) to induce asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…However, no studies have investigated the effect of chronic hypergravity in animals with allergic disorders. In our previous study, mice with allergic asthma showed no significant change in serum OVA-specific IgE after exposure to short-term hypergravity (10G for 4 hours) 20 . Therefore, we could suggest that changes in the allergic response in animals with allergic disorders may be unrelated to IgE-related mechanisms.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, no studies have investigated the effect of chronic hypergravity in animals with allergic disorders. In our previous study, mice with allergic asthma showed no significant change in serum OVA-specific IgE after exposure to short-term hypergravity (10G for 4 hours) 20 . Therefore, we could suggest that changes in the allergic response in animals with allergic disorders may be unrelated to IgE-related mechanisms.…”
Section: Discussionmentioning
confidence: 83%
“…After exposure to short-term hypergravity, serum titers of IL-1β showed no significant change20. On the other hand, Liu and colleagues reported that IL-1β titers in rat brain were significantly increased after short-term exposure to hypergravity of 14G22.…”
Section: Discussionmentioning
confidence: 98%
“…It might be the result of a stress response to rotatory stimuli. Another interesting aspect of this research is that, Jang et al [7] suggested that changes in the allergic response in animals with allergic disorders may be unrelated to IgE-related mechanisms, because of the study showed no significant change in serum OVA-specific IgE after exposure short term hypergravity (10 G for 4 hours).…”
Section: Impacts Of Thementioning
confidence: 86%
“…A possible explanation for our results may be that the increased IL10 gene expression may represent a delicate regulatory pathway to restore the homeostasis under inflammatory conditions. Thus, IL10 may be a surrogate marker of a heightened inflammatory process and act to counterregulate the effects of proinflammatory mediators [ 35 , 40 ]. In regard to the correlation analysis, we demonstrated that IL10 gene expression was significantly positively correlated with lipid parameters and also with physical and glycemic parameters.…”
Section: Discussionmentioning
confidence: 99%